Asymptomatic bacteriuria is an independent predictor of urinary tract infections in an ambulatory cirrhotic population: a prospective evaluation. (7th January 2014) - Ye, Carrie; Kumar, Deepali; Carbonneau, Michelle; Keough, Adam; Ma, Mang; Tandon, Puneeta
Abstract Background & Aims Asymptomatic bacteriuria (ASB) is a risk factor for urinary tract infections (UTIs) in many patients without liver disease. It remains unclear whether a diagnosis of ASB in an outpatient with cirrhosis could be utilized to predict the subsequent development of a UTI. We undertook this study to determine the prevalence and incidence of ASB in an outpatient population and its association with UTI. Methods We prospectively evaluated 108 adult outpatients with cirrhosis over a 6‐month period. Monthly midstream urines (MSU) were performed to detect the occurrence of UTI and ASB (culture of ≥108 CFU/L of a urinary pathogen in the absence of UTI symptoms). Results Of 108 patients enrolled, 99 completed at least one MSU, for a total of 489 MSUs. Total follow‐up was 44 person‐years. The incidences of ASB and UTI were 181 and 250 per 1000 person‐years, respectively. The prevalences of ASB and UTI on the first MSU were 5 and 1%, respectively. In total, 8% of patients developed an episode of ASB and 11% developed a UTI during the study period. Univariate predictors of UTI were female gender, primary biliary cirrhosis, number of previous UTIs and preceding ASB. Preceding ASB was the only independent predictor of UTI on multivariate analysis, with an odds ratio of 6.2 (1.1–34.3), P = 0.04. Conclusions Cirrhotic patients have higher rates of ASB and UTI than reported in the general population. ASB is an independent predictor of UTI. Further studies are necessary to determine whether routine screening and antimicrobial treatment of ASB is warranted.